Minds, Models and Milieux Commemorating the Centennial of the Birth of Herbert Simon - Frantz, Roger; Marsh, Leslie; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book is a collection of specially commissioned chapters from philosophers, economists, political and behavioral economists, cognitive and organizational psychologists, computer scientists, sociologists and permutations thereof as befits the polymathic subject of this book Herbert Simon.
Keywords: Economic history; Economic theory; Behavioral economics; Economics; Behavioral/Experimental Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Economic History; Methodology/History of Economic Thought; Electronic books